Digital Innovation Practices of Islamic Education Teachers in Learning Media Utilization - Setiawan, Dimas; Setiawan, Hasrian Rudi; Nst, Wildan Akhir; Zen, Aura Maritza (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze the digital innovation practices of Islamic Education teachers in utilizing learning media. In the era of digital transformation, teachers are required to integrate technology into the learning process to enhance interactive, effective, and relevant learning experiences for students. This research employed a qualitative approach with a descriptive study method. The participants were Islamic Education teachers at the secondary school level. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that teachers’ digital innovation practices include the use of various digital learning platforms, the development of interactive media, and the utilization of game-based and multimedia applications. Supporting factors include teachers’ digital competence and institutional support, while challenges involve limited infrastructure and technological literacy. This study concludes that digital innovation in learning media utilization plays a significant role in improving the effectiveness of Islamic Education learning.